ANALISIS LOGO HARI ULANG TAHUN KOTA SEMARANG KE-469 HASIL KARYA IBNU PRAMUDYA - Aliya, fibriyani Nur (Interaksi: Jurnal Ilmu Komunikasi, 2017)
Abstract The logo of Semarangâ€™s 469th birthday celebration was created by Ibnu Pramudya, the winner of Logo Competition held by the town council of Semarang. The current version of Semarangâ€™s 469th birthday celebration logo consists of number 4,6, and 9 combined together in a unique curve with gradation of red and yellow. The committees and the judges of the competition have requirements for the chosen logo that it must be able to show the vision and mission of Semarang and based on the theme of Semarangâ€™s 469th birthday celebration â€œBulatkan Tekat, Semarang Hebatâ€. The research question would be whether the logo created by Ibnu Pramudya was qualified enough according to the judges and represented the soul of Semarang. By using Semiotic Theory of Charles Sanders Peirce, this logo was analyzed based on the symbols, the used of symbols, and interpreters. It was found that the numbers of 469 created by Ibnu Pramudya was not only unique and attractive, but also it could meet the committeesâ€™ and judgesâ€™ qualifications. This attractive logo could represent unity and harmony the people of Semarang in developing the city, so that met the qualification of the theme of Semarangâ€™s 469th birthday celebration, â€œBulatkan Tekad, Semarang Hebatâ€. This showed that the message through the logo could be interpreted by the interpreters. Key words: Semiotic, logo, Semarangâ€™s 469th birthday celebration, Charles Sanders Peirce